2015
DOI: 10.1111/1750-3841.13102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Capacity of Brazilian Passiflora Seed Oils

Abstract: The seed oils of different varieties of 4 Passiflora species cultivated in Brazil were analyzed and compared regarding their physicochemical parameters, fatty acid composition and the presence of minor components, such as phytosterols, tocopherols, total carotenoids, and phenolic compounds. The antioxidant capacities of the oil extracts were determined using the 2,2'azinobis [3-ethylbenzothiazoline-6-sulfonic acid] and oxygen radical absorbance capacity methods. The results revealed that all studied Passiflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
(61 reference statements)
5
21
1
3
Order By: Relevance
“…Dther fruits and seeds from Cerrado exhibited higher carotenoid concentration than soursop and marolo seeds. According to Silva et al (2014a), jatobá-do-cerrado flour contains 17000 µg β-carotene kg -1 ; Santana et al (2015) analyzed the seeds of sweet passionfruit (Passiflora alata) and found 129260 µg β-carotene kg -1 (d.b. ); Dliveira et al (2017) reported 6921 µg β-carotene kg -1 of oil for pequi (Caryocar brasiliense) almond.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Dther fruits and seeds from Cerrado exhibited higher carotenoid concentration than soursop and marolo seeds. According to Silva et al (2014a), jatobá-do-cerrado flour contains 17000 µg β-carotene kg -1 ; Santana et al (2015) analyzed the seeds of sweet passionfruit (Passiflora alata) and found 129260 µg β-carotene kg -1 (d.b. ); Dliveira et al (2017) reported 6921 µg β-carotene kg -1 of oil for pequi (Caryocar brasiliense) almond.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…The composition of fatty acids in gastrocnemius muscle (100 mg) was determined by gas chromatography, according methods previously described (Feldsine et al 2002;Ratnayake et al 2002). A similar procedure has been used in our studies (Afonso et al 2013;Hirabara et al 2013;Fariña et al 2014;de Santana et al 2015). The results are presented as the mean ± SD of four animals per group.…”
Section: Determination Of Gastrocnemius Muscle Fatty Acid Compositionmentioning
confidence: 99%
“…PS pulp and seeds have recently been identified as rich in BC, particularly in C-glycosides of flavonoids [18], and also homoorientin, vitexin, isovitexin, and orientin at higher contents than those found in Passiflora edulis, açaí (Eurydema oleracea), and orange juice [19]. They have also revealed antioxidant and antimicrobial properties in vitro [20,21]. These effects are potentially due to the presence of vitamin E and BC such as terpenoids, polyamines, and polyphenols, especially orientin, isoorientin, vitexin, and isovitexin [17][18][19]21].…”
Section: Introductionmentioning
confidence: 99%